2023
DOI: 10.3390/nu15204477
|View full text |Cite
|
Sign up to set email alerts
|

Water Intake and Handgrip Strength in US Adults: A Cross-Sectional Study Based on NHANES 2011–2014 Data

Dongzhe Wu,
Chaoyi Qu,
Peng Huang
et al.

Abstract: This study aimed to examine the relationship between daily total intake of water (DTIW) and handgrip strength (HGS) among US adults and to explore the impact of water intake on muscle function and health, providing a reference for public health policies and health education. Using the data from the National Health and Nutrition Examination Survey (NHANES) 2011–2014, a cross-sectional survey design was adopted to analyze 5427 adults (48.37% female and 51.63% male) aged 20 years and above. DTIW was assessed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…In line with the results from the present study, a recent survey among 2233 Chinese residents in 27 cities reported a significantly higher TFI in males than females regardless of age group [ 21 ]. Wu et al [ 22 ] also found a significant difference in daily TWI between US males and females based on the National Health and Nutrition Examination Survey 2011–2014 data. According to the results of the GEE analysis, gender was significantly associated with TDF.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the results from the present study, a recent survey among 2233 Chinese residents in 27 cities reported a significantly higher TFI in males than females regardless of age group [ 21 ]. Wu et al [ 22 ] also found a significant difference in daily TWI between US males and females based on the National Health and Nutrition Examination Survey 2011–2014 data. According to the results of the GEE analysis, gender was significantly associated with TDF.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate water intake helps maintain the balance of intracellular and extracellular fluids, promotes smooth blood circulation, enhances the delivery efficiency of nutrients and hormones, supports normal nervous system function, and improves the excitability and conduction speed of motor neurons. This, in turn, increases the contractile capacity and strength of muscle fibers [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total cholesterol concentration ≥ 200 mg/dL, triglyceride concentration ≥ 150 mg/dL, male HDL concentration < 40 mg/dL, female HDL concentration < 50 mg/dL, and low-density lipoprotein cholesterol concentration ≥ 130 mg/dL were the criteria for hyperlipidaemia. Additionally, the use of cholesterol-lowering drugs was also defined as hyperlipidaemia [21].…”
Section: Definition Of Covariablesmentioning
confidence: 99%